Removal of Methylene Blue From Aqueous Solutions by Adsorption on Alum Sludge: Effect of Operating Parameters - Sandyanto Adityosulindro; Annisa Firdaus; Djoko Mulyo Hartono (Jurnal Serambi Engineering, 2024)
In developing countries, high capital, operational costs, limited space are the main challenges to implement appropriate sludge treatment system. Thus, research about reutilization sludge are urgently needed. In this study, alum sludge from sedimentation basin of water treatment plant was dried and used as adsorbent for removal methylene blue from aqueous solutions. Alum sludge was charachterized by SEM-EDX, XRD, FTIR, particle size analyzer, surface area analyzer and pHPZC. The effect of various parameters such as: contact time (5-360 min), initial MB concentrarion (5-100 mg/L), adsorbent dosage (0.25-3.0 g/L), pH (4-10), temperature (20-60 0C) and water matrix (deionized, sedimentation basin effluent, river water, wastewater) were assessed. The result showed that removal efficiency has directly proportional with contact time, adsorbent dosage and pH, while an inverse relationship with initial MB concentration was observed. Removal efficiency up to 98% was achieved at MB 50 mg/L, AS 3 g/L, temperature 300, and pH 6.8. Isotherm and kinetic models fitted Langmuir model with capacity of 37.45 mg/g and pseudo-second-order model kinetic. Applicability test in various water matrix indicated that the utilization of low-cost adsorbent from non-modified dried alum sludge has potential for removal of methylene blue from low to moderate contaminated aqueous solution.